TRANSTHYRETIN POLYNEUROPATHY (CLINICAL CASE) - Наталья Викторовна Коробкова; Светлана Алексеевна Зуева; Ольга Валерьевна Рохленко; Вадим Гельевич Мозес; Елена Владимировна Рудаева; Светлана Ивановна Елгина; Кира Борисовна Мозес; Яэль Центер; Наталья Степановна Черных (Медицина в Кузбассе, 2023)
Amyloidosis is a violation of protein metabolism, accompanied by the formation in tissues of a specific protein-polysaccharide complex (amyloid) of a fibrillar structure, characterized by a high orderliness of fibrils 5-10 nm thick due to the abundance of β-folded conformation in the secondary structure of the main amyloid-forming protein. The modern classification of amyloidosis is based on the principle of specificity of the main fibrillar amyloid precursor protein. Today, more than 36 amyloid precursor proteins have been identified in various human amyloidoses, among which at least 10 hereditary forms are distinguished. Among the listed hereditary forms, the most common is transthyretin amyloidosis (from the English. Amyloidosis transthyretin, ATTR): a fatal systemic progressive disease, manifested mainly by severe polyneuropathy, autonomic dysfunction and heart damage. Death occurs within 7-12 years from the onset of the disease in the absence of adequate treatment.